History Heroism Commander Gocah in the Kingdom of Aru - Firmansyah, Sutan Raja Hendi; Rohani, Laila (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
The purpose of this study is to find out the history of the commander Gocah of the Aru kingdom. The method used is the historical method. The research results show that the Aru Kingdom is the oldest kingdom in North Sumatra, which has existed on the east coast of North Sumatra Province now since the 13th-16th century AD. The Karo people say that Aru is Aru which comes from the said Karo. This research method uses qualitative techniques with a descriptive approaches to describe the heroic history of Panglima Gocah and the Kingdom of Aru. The results showed that the Clan twins formed the Aru community, which is the Karo community. The Kembaren clan is thought to have originated from Pagaruyung in Minangkabau Land, there are rumors that the Kingdom of Aru and the Kingdom of Pasai (Aceh) often clashed. The Aru attacked Pasai in the early 16th century and massacred a large number of the local population. However, Pasai retaliated against the attack. Aceh was able to penetrate the fortress of the Kingdom of Aru with a series of attacks. Aceh had sent powerful military expeditions to the kingdom of Deli on several occasions to maintain power. In the end, Aceh appointed its commander as Major of the State in an attempt to increase its politics influence and keep Deli from escalating rebellions. It was Seri Paduka Gocah Pahlawan who became this commander, he was a pioneer in the history of the Deli Sultanate.